2022
DOI: 10.3390/ijgi11070377
|View full text |Cite
|
Sign up to set email alerts
|

Revealing Taxi Interaction Network of Urban Functional Area Units in Shenzhen, China

Abstract: Characterizing the taxi travel network is of fundamental importance to our understanding of urban mobility, and could provide intellectual support for urban planning, traffic congestion, and even the spread of diseases. However, the research on the interaction network between urban functional area (UFA) units are limited and worthy of notice. Therefore, this study has applied the taxi big data to construct a travel flow network for the exploration of spatial interaction relationships between different UFA unit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 49 publications
0
4
0
Order By: Relevance
“…The recognition of public services and commercial and related sub-classes has positive significance for urban facilities construction improvement and hot spot detection [ 57 , 58 ]. In addition, the distribution of fine functional areas has certain reference value for the analysis of the causes of traffic congestion [ 59 ], the evaluation of regional functional use intensity [ 23 ], and the planning calibration [ 60 ] and renewal of cities [ 61 ]. Some scholars have also finely classified UFAs, but the data sources were different [ 5 , 23 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…The recognition of public services and commercial and related sub-classes has positive significance for urban facilities construction improvement and hot spot detection [ 57 , 58 ]. In addition, the distribution of fine functional areas has certain reference value for the analysis of the causes of traffic congestion [ 59 ], the evaluation of regional functional use intensity [ 23 ], and the planning calibration [ 60 ] and renewal of cities [ 61 ]. Some scholars have also finely classified UFAs, but the data sources were different [ 5 , 23 , 62 ].…”
Section: Discussionmentioning
confidence: 99%
“…Using various traffic flow data and spatial network approaches, researchers have extensively explored urban travel patterns and traffic networks from the perspective of traffic demand [54][55][56]. By leveraging big data, including mobile phone, smart card, floating vehicle, and social media data, researchers can analyze user movement data as traffic flows on networks, thereby creating weighted networks that reveal the structure and related properties of UTNs [57][58][59]. Some studies have shown that complex network analysis based on various types of emerging traffic flow data can effectively reveal urban traffic demand and its dynamics [11,60].…”
Section: Related Workmentioning
confidence: 99%
“…Currently, there are many studies on spatial interaction patterns between provinces, cities, within provinces and cities [14][15][16], or urban agglomeration [17], while there is less research on spatiotemporal interaction patterns at the local scale of functional areas [18]. Existing methods mainly focus on the detection of explicit spatial interaction patterns [3], such as clusters in origin-destination (OD) flow data [19][20][21], without gaining insight into the implicit underlying travel demands of the residents moving between different urban areas [19,22].…”
Section: Introductionmentioning
confidence: 99%